PERFORMANCE SIMULATION SYSTEM SEPARATION L- V (G ) MULTICOMPONENT MULTISTAGE - Chuquilín-Terán, C. (1999)
In this paper the simulation of separation systems LV ( G) for simple multistage multicomponent absorbers and absorbers with reboiler , where mixtures are considered ideal behavior and distillation processes is studied which mixtures can be considered ideal or not with behavior ideal. The simulation of such separation process is performed using the Newton -Raphson method numerical 2N . For non-ideal mixtures the activity coefficient is used in the liquid phase , which is evaluated from thermodynamic models : Wilson, NRTL , UNIQUAC and UNIFAC . In this paper the mathematical model and simulation program developed for the separation of these processes is described. A variety of examples have been used to test the functionality of the program. The results produced by the program are compared with those for the CHEMCAD III. It has also conducted sensitivity analysis for the initial temperature profile and the constant relating to the increase of the independent variables in order to see its influence on the rate of convergence of the solution. In distillation columns which are considered non-ideal behavior are analyzed initial sensitivity profile and composition of binary interaction parameters . Finally , we have studied the influence of operating variables on the quality of the product .